Safety Climate Assessment in Operating Room Nurses Through Safety Attitudes Questionnaire (SAQ) - Rubén J. Tejera-Quintana; Pilar Marqués-Sánchez; C. Patricia Arencibia-Sánchez; Elba Mauriz (Colegio de Enfermería de Caceres, 2018)
Introduction: Surgical safety is a global public health concern. The attitudes and perceptions of the surgical team regarding to the patient safety are associated to the safety climate and the prevalence of adverse events. Objective: To describe the safety climate according to sociodemographic characteristics and work professional conditions of operating room nurses from three Hospitals in Canary Islands, Spain. Method: This work presents a multicentre cross-sectional study. Data collection was obtained by means of The Safety Attitudes Questionnaire (SAQ), a self-completed questionnaire translated to the Spanish. A convenience sample with voluntary participation was selected. The safety climate was determined through six factors: Teamwork climate, Safety climate, Job satisfaction, Perception of the Unit and Hospital Management, Working conditions and Stress recognition. Results: The SAQ domains show variability in relation to sociodemographic characteristics and work professional conditions. Perception of the management and Working conditions are the domains lower valued in every sociodemographic characteristics studied. The size of the hospitals and Years of professional experience showed statistical differences in several domains. Conclusions: The age, years of profession, years of experience and type of hospital present strong relationship among patient safety perception.